2019
DOI: 10.3389/fimmu.2019.00778
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Type I Interferons in Infectious Immunity: Plasmacytoid Dendritic Cells Not Always in the Driver's Seat

Abstract: Type I Interferons (IFNs) are hallmark cytokines produced in immune responses to all classes of pathogens. Type I IFNs can influence dendritic cell (DC) activation, maturation, migration, and survival, but also directly enhance natural killer (NK) and T/B cell activity, thus orchestrating various innate and adaptive immune effector functions. Therefore, type I IFNs have long been considered essential in the host defense against virus infections. More recently, it has become clear that depending on the type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 199 publications
(265 reference statements)
5
108
0
Order By: Relevance
“…69 Our studies and others similarly suggest that pathological type I IFN production in SLE is not limited to pDCs. 69 Our studies and others similarly suggest that pathological type I IFN production in SLE is not limited to pDCs.…”
Section: Pathogenic Effects Of Pdcssupporting
confidence: 66%
See 2 more Smart Citations
“…69 Our studies and others similarly suggest that pathological type I IFN production in SLE is not limited to pDCs. 69 Our studies and others similarly suggest that pathological type I IFN production in SLE is not limited to pDCs.…”
Section: Pathogenic Effects Of Pdcssupporting
confidence: 66%
“…pDCs are often considered the principal source of type I IFNs in vivo; however, it is becoming clear that production of type I IFN, especially the rapidly induced high-affinity IFNβ, is accomplished a variety of cell types and cannot be mainly attributed to pDCs. 69 Our studies and others similarly suggest that pathological type I IFN production in SLE is not limited to pDCs. 1,67,[70][71][72] pDCs have long been prime suspects owing to a large body of literature confirming their high capacity for type I IFN production following viral infection or stimulation with viral nucleic acid mimics.…”
Section: Pathogenic Effects Of Pdcssupporting
confidence: 66%
See 1 more Smart Citation
“…However, none of the bovine studies conclusively demonstrated the main source of IFNs was pDC. Recent findings in mouse models indicate that pDC may have been overestimated in regard to their importance for early IFN type I production and highlight other sources [97]. Additionally, when human pDC were stimulated on a single‐cell basis, only a small fraction was capable of IFN‐α production (<0.02% IFN‐α‐producing pDCs) [98].…”
Section: Discussionmentioning
confidence: 99%
“…Under homeostatic conditions, most cells produce moderate amounts of type I IFN, but specialized cells of the immune system, mainly plasmacytoid dendritic cells (pDCs), produce high amounts when activated [123][124][125]. All type I IFNs signal through a ubiquitously expressed receptor composed of the IFNAR1 and the IFNAR2 chain (Table 1).…”
Section: Type I Ifnsmentioning
confidence: 99%